Pengaruh Pembiayaan Modal Usaha Terhadap Peningkatan Usaha Nasabah di Koperasi Simpan Pinjam Pembiayaan Syariah Baituk Mall Wattanwil Nuansa Ummah Jawa Timur Cabang Utama - Nashar (Al-Buhuts, 2020)
The main branch of the BMT NU Sharia Financing Savings and Loan Cooperative is a bank that implements sharia principles. One of the most important differentiations that Islamic banks must have is having a strategy to retain customers who make loans by means of excellent service, mentoring and education, and emotional relationships. Based on the results of observations, there is a distinct uniqueness of the business capital financing of the Sharia Credit and Savings and Loan Cooperative Cooperative of BMT NU East Java Main Branch. The purpose of this writing is curiosity and wants to interpret the correlation of venture capital financing to increase the business of cooperative members in KSPP. Syariah at Baitul Mall Wattanwil (BMT) Nuansa Ummah East Java Main Branch, as well as to obtain empirical data on whether or not there is an effect of venture capital financing on increasing customer business at KSPP. Syariah BMT NU East Java Main Branch. This result uses a quantitative approach with simple linear regression analysis techniques with the help of SPSS 20 analysis tool. While the hypothesis testing uses the t test calculation. The population in this study amounted to 35 customers. Samples use saturated or census samples. Data collection techniques using, questionnaire (questionnaire). The results showed that: first, with the t test the variable of venture capital financing showed 0.000 smaller than a (0.000 <0.05). Value of tcount> ttable (7,909> 1.68957). This means that business capital financing has a significant effect on business improvement. Second, the R Square value is 0.655 or 65.5%. This means that 65.5% of the regression model in this study explains the dependent variable (Business Increase), while the remaining 34.5% is influenced by variables not taken into account in the study